Exploring the antecedents of entrepreneurial intention on Turkish university students - YURTKORU, EMİNE SERRA (ELSEVIER SCIENCE BV, 2014)
Present study aims to explore the impact of contextual factors on entrepreneurial intention of university students. Theory of Planned Behavior Model (TPB) is used as a theoretical framework, since recent literature suggests that intentions can predict future entrepreneurship. Contextual factors which are relational, educational and structural support are considered as antecedents of personal attitude and perceived behavioral control, in return they are expected to have an impact on entrepreneurial intention. The model is tested on 425 university students. Our results provide useful implications for policy makers and educators. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Entrepreneurial intention; theory of planned behavior; subjective norm; perceived attitude; perrceived behavioral control; educational support; structural support; relational support